Extracellular recording of direct synaptic signals with a CMOS-nanoelectrode array. Issue 17 (5th August 2020) - Abbott, Jeffrey; Ye, Tianyang; Krenek, Keith; Gertner, Rona S.; Wu, Wenxuan; Jung, Han Sae; Ham, Donhee; Park, Hongkun
Abstract : In this work, we use extracellular nanoelectrode arrays to non-invasively map, record, and stimulate in vitro rat neurons and their synaptic connections. Abstract : The synaptic connections between neurons are traditionally determined by correlating the action potentials (APs) of a pre-synaptic neuron and small-amplitude subthreshold potentials of a post-synaptic neuron using invasive intracellular techniques, such as patch clamping. Extracellular recording by a microelectrode array can non-invasively monitor network activities of a large number of neurons, but its reduced sensitivity usually prevents direct measurements of synaptic signals. Here, we demonstrate that a newly developed complementary metal-oxide-semiconductor (CMOS) nanoelectrode array (CNEA) is capable of extracellularly determining direct synaptic connections in dense, multi-layer cultures of dissociated rat neurons. We spatiotemporally correlate action potential signals of hundreds of active neurons, detect small (∼1 pA after averaging) extracellular synaptic signals at the region where pre-synaptic axons and post-synaptic dendrites/somas overlap, and use those signals to map synaptic connections. We use controlled stimulation to assess stimulation-dependent synaptic strengths and to titrate a synaptic blocker (CNQX: IC50 ∼ 1 μM). The new capabilities demonstrated here significantly enhance the utilities of CNEAs in connectome mapping and drug screening applications.